CHARACTERIZATION OF AMMONIOLEUCITE (NH4 [ALSI2O6] AND ND4-AMMONIOLEUCITE (ND4[ALSI2O6] USING IR SPECTROSCOPY AND RIETVELD REFINEMENT OF XRD SPECTRA - Andrut M.; Harlov D.E.; Najorka J. (My University, 2004)
Ammonioleucite (NH4)[AlSi2O6] and its deuterated analogue ND4-ammonioleucite (ND4)[AlSi2O6] have been synthesised in 20 – 150 mg amounts at 300 oC and 500 MPa in 5 mm wide, 4 cm long Au capsules using Rene’ metal hydrothermal autoclaves. The resultant product consists of 20 – 30 μm size single tetragonal crystals as well as 50 – 100 μm wide clumps of ingrown crystals. IR spectra obtained from powdered samples are assigned on the basis of Td symmetry for both the ammonium and deutero-ammonium ion. They show triply degenerate vibrational bands (i.e. ν3 and ν4), some overtones, and combination modes from NH4+ and ND4+. While Td symmetry for NH4+ in ammonioleucite is not strictly correct due to distortion of the NH4+ molecule, the non-cubic field is not large enough at room temperature to cause a substantial splitting in the bands. However, this perturbation is documented in the IR-spectra by a substantial increase in the FWHH as well as the occurrence of shoulders on the broadened bands. In contrast, at lower temperatures the observed band splittings in the former triply degenerated states of ν3 and ν4 could be explained by an effective local field with D2 symmetry. Rietveld refinement indicates that ammonioleucite, like leucite, has a tetragonal structure with space group symmetry I41/a. Here the NH4+ molecule replaces the K+ cation on the 8-fold co-ordinated W site, which has m symmetry. Substitution of NH4+ for K+ in the leucite structure results in an increase of the cell parameter a, whereas c is slightly reduced. The mean bond length of ammonioleucite is increased in comparison to leucite from 3.00 Å to 3.12 Å whereas the mean bond length of 1.65 Å remains unchanged. This results in an increase in the volume of the polyhedron hosting the NH4+ molecule as well as a decrease in distortion for structural channels parallel to the <111> direction, formed by the arrangement of the six-fold rings, on which the W cations are located. The same effect is also observed, in general, when Rb+ or Cs+ is substituted for K+ in leucite.
Keywords: Ammonioleucite